2021
DOI: 10.3390/plants10061159
|View full text |Cite
|
Sign up to set email alerts
|

Herbicidal Effects and Cellular Targets of Aqueous Extracts from Young Eucalyptus globulus Labill. Leaves

Abstract: Eucalyptus globulus Labill. is a widespread exotic species that contributes to the formation of fire-prone environments, a great concern under climate change conditions. Therefore, sustainable practices to help locals managing eucalyptus stands are needed. In this perspective, harnessing eucalyptus’ specialized metabolism as a source of allelochemicals can be a promising approach for weed control. Thus, the main goals of this work were to evaluate the herbicidal potential of post-fire regenerated E. globulus l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Therefore, the allelopathic compatibility between crops and Eucalyptus trees must be essentially checked to avoid the potential adverse effects of trees on the associated crops. Additionally, the aqueous extract of the oven-dried leaves has a herbicidal potential as a biocide against the widespread weed of Portulaca oleracea L., which is attributable to the existence of a significant amount of allelochemicals [86]. The above-mentioned results recommend that the bioactive compounds present in Eucalyptus plants must be further investigated in weed control, as bioherbicides, with possible commercial applications.…”
Section: Eco-friendly Approaches For Application Of E Globulusmentioning
confidence: 99%
“…Therefore, the allelopathic compatibility between crops and Eucalyptus trees must be essentially checked to avoid the potential adverse effects of trees on the associated crops. Additionally, the aqueous extract of the oven-dried leaves has a herbicidal potential as a biocide against the widespread weed of Portulaca oleracea L., which is attributable to the existence of a significant amount of allelochemicals [86]. The above-mentioned results recommend that the bioactive compounds present in Eucalyptus plants must be further investigated in weed control, as bioherbicides, with possible commercial applications.…”
Section: Eco-friendly Approaches For Application Of E Globulusmentioning
confidence: 99%
“…This suggests a high potential interest in dried leaf extracts, especially from young trees, for use as a natural herbicide. In fact, in a recent study, it was revealed that aqueous extracts prepared with dried leaves from young E. globulus foliar-applied, twice-a-week at 250 g L -1 had potent herbicidal activities against purslane seedlings, used as a model weed species ( Pinto et al., 2021 ). The differences in the content of hydrolysable tannins in the tested extracts were pointed out as a possible cause for the high allelopathic activity of dried E. globulus leaf extracts when compared with that of fresh leaf extracts.…”
Section: Discussionmentioning
confidence: 99%
“…One of these portions was immediately oven-dried at 60°C until reaching a constant weight. Then, fragments of fresh and dried leaves from young and mature trees collected in the three different sites (i.e., Y1, Y2, Y3, A1, A2, and A3 from Figure 1 ) suffered an extraction procedure in deionized water at 70°C, for 30 min, according to the methodology of Pinto et al. (2021) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding soil management, tillage, stale seedbed, and dead mulches have been proposed to reduce infestations and seedbank presence (Pinke et al, 2018 ; Jensen, 2019 ; Menegat and Nilsson, 2019 ; Fracchiolla et al, 2021 ; Nikolić et al, 2021 ; Zeller et al, 2021 ). Mowing, hoeing, and flaming (Gerhards et al, 2020 ;Mainardis et al, 2020 ;Spaeth et al, 2020 ;Hofmeijer et al, 2021 ), as well as the use of beneficial microorganisms, biocontrol agents and bioherbicides (Boari et al, 2016 ; Giannini et al, 2021 ; Pinto et al, 2021 ) could be used in site-specific direct control. Finally, state-of-the-art artificial intelligence technologies, weed mapping, and decision support systems (DSS) facilitate the monitoring of weed communities, and the rapid and informed decision-making (Sønderskov et al, 2015 ; Halstead et al, 2021 ; Jurado-Expósito et al, 2021 ).…”
Section: Reducing the Herbicide Use Sustainablymentioning
confidence: 99%